Nitrogen Regulation of Root Branching - WALCH-LIU, PIA (Oxford University Press, 2006)
• Background Many plant species can modify their root architecture to enable them to forage for heterogeneously distributed nutrients in the soil. The foraging response normally involves increased proliferation of lateral roots within nutrient-rich soil patches, but much remains to be understood about the signalling mechanisms that enable roots to sense variations in the external concentrations of different mineral nutrients and to modify their patterns of growth and development accordingly. • Scope In this review we consider different aspects of the way in which the nitrogen supply can modify root branching, focusing on Arabidopsis thaliana. Our current understanding of the mechanism of nitrate stimulation of lateral root growth and the role of the ANR1 gene are summarized. In addition, evidence supporting the possible role of auxin in regulating the systemic inhibition of early lateral root development by high rates of nitrate supply is presented. Finally, we examine recent evidence that an amino acid, l-glutamate, can act as an external signal to elicit complex changes in root growth and development. • Conclusions It is clear that plants have evolved sophisticated pathways for sensing and responding to changes in different components of the external nitrogen supply as well as their own internal nitrogen status. We speculate on the possibility that the effects elicited by external l-glutamate represent a novel form of foraging response that could potentially enhance a plant's ability to compete with its neighbours and micro-organisms for localized sources of organic nitrogen.